2020
DOI: 10.1177/0891988720973749
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Antidepressant Treatment and Outpatient Rehabilitation Within the First Year After Stroke

Abstract: This study aims to identify individual determinants of antidepressant treatment and outpatient rehabilitation after stroke. People with ischemic stroke ( N = 303) recruited at 2 inpatient rehabilitation clinics were included into a prospective longitudinal study with follow-up telephone interviews 6 and 12 months later. Participants reported on their use of antidepressant medication and psychotherapy as well as physical, occupational, speech, and neuropsychological therapy. The use of antidepressants at discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(90 reference statements)
0
4
0
Order By: Relevance
“…ADT represents an ef-fective agent for PSD treatment [9][10][11][12] and is part of established stroke guidelines recommendations [14,15]. Moreover, previous studies showed an association between more severe PSD and higher treatment rates, possibly due to easier detection and a higher need [7,45]. Therefore, our findings indicate that with regard to severity, the mismatch between ADT and PSD might be more pronounced in later parts of the medical supply chain or clinical practice, which more likely do not have a primary focus on PSD and its consequences for stroke survivors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ADT represents an ef-fective agent for PSD treatment [9][10][11][12] and is part of established stroke guidelines recommendations [14,15]. Moreover, previous studies showed an association between more severe PSD and higher treatment rates, possibly due to easier detection and a higher need [7,45]. Therefore, our findings indicate that with regard to severity, the mismatch between ADT and PSD might be more pronounced in later parts of the medical supply chain or clinical practice, which more likely do not have a primary focus on PSD and its consequences for stroke survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Participants: Stroke survivors were recruited from two German rehabilitation centers. The examined participants stem from the prospective longitudinal "Berlin PSD study" (for a comprehensive description see [7,37]). Inclusion criteria were (1) occurrence of ischemic stroke diagnosed in medical record within six months before baseline assessment, (2) sufficient verbal comprehension as defined by a score of ≤12 error points in Aachener Aphasie Test (AAT) [38].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis is based on the data of two independent prospective longitudinal studies, the Berlin PSD study and the PoStDAM study (=Post-Stroke Depression: Early Assessment for improved Management). Both studies' procedures were previously described in detail ( 12 , 34 ) and are summarized in the following. Patient flow and reasons for drop-out are reported in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…De manera más concreta, solo entre el 23 y el 49% de los supervivientes a un ictus que presentaron síntomas depresivos clínicamente relevantes habían recibido tratamiento antidepresivo en los 12 meses siguientes al ictus 25,36,38 . En aquellos pacientes con DPI tratados con antidepresivos, los resultados de diferentes estudios muestran una asociación entre mayor severidad de la DPI y mayores tasas de uso de antidepresivos, posiblemente debido a una mayor facilidad para su detección y una mayor necesidad de tratamiento 39 .…”
Section: Depresión Post-ictusunclassified